Experiência de vida e de (re)existência de mulheres negras quilombolas da Serra do Evaristo - Lima, Juliana Murta de (2024)
In a capitalist and patriarchal society, black people, women and children are the biggest victims of the processes resulting from social inequality. When placed within an intersectional perspective, the context becomes even more painful for black quilombola women, as they are simultaneously crossed by different forms of oppression, namely racism, sexism and, consequently, classism. In this context, the starting question for this study was: "How does the intersection of racism and sexism as authoritarian practices affect the life experience and (re)existence of black quilombola women? ", which was answered through the operationalization of the objectives of this research: a) Describe the relationship between authoritarianism and racism b) Identify the authoritarian bases of sexism; c) Analyze how these oppressions affect the life experiences of these women and d) Understand how these women mean and articulate the processes of (re)existence in the face of these categories of oppression in their similarities and/or differences. The reflections of the research are anchored in a) Critical Race Theory; b) Studies on Black Feminism and c) Quilombism. The methodology adopted is of a theoretical-bibliographical and qualitative nature, using the following resources: a) Field Diary and b) Autobiographical Narrative Interview. The theory of Critical Discourse Analysis was used to analyze the data collected in the interviews, and the text was tabulated using Atlas Ti qualitative research software. As conclusions, we understand that racism and sexism are even more violent with black quilombola women and that living in a community is a protective factor for them and a space for developing both individual and community resistance strategies. This study has contributed to the dismantling of a white, Eurocentric science and to the fight for more black women in scientific production spaces and in academy.